Congenital granular cell tumor of the newborn - Spontaneous regression or early surgical intervention - Ankita Dhareula; Manojkumar Jaiswal; Ashima Goyal; Krishan Gauba (Wolters Kluwer Medknow Publications, 2018)
Congenital granular cell tumor of the newborn is a benign, relatively innocuous hamartomatous lesion arising from the alveolar ridge. Large lesions often warrant prompt surgical removal owing to the associated difficulty in breastfeeding and respiration of the infant. However, for medium-sized lesions, another approach could be observed for spontaneous regression. The present case report highlights the use of a combination approach for management of tumor in a 2-day-old female child presenting with a large protruding mass from the mouth associated with difficulty in breastfeeding. A combination of observation for regression in size followed by electrosurgical removal of the tumor was done. The infant was followed up regularly over a long period of 3 years to assess any adverse effects of surgical intervention on the maxillary primary anterior dentition of which none were recorded.